Gravitational Lensing as a Window into the Distant Universe: The Complex Interplay of Gravity and Plasma in Lensing Effects - Mohamed Emtir (AlQalam Journal of Medical and Applied Sciences, 2025)
In this article, we provide a summary of recent advancements concerning the influence of plasma on gravitational lensing effects. The bending of light due to gravity and plasma results from a complex interplay of different physical factors: gravity, dispersion, and refraction. In a non-uniform plasma, chromatic refraction also occurs. We explore chromatic effects in strong gravitational lensing configurations, focusing on the variation in the angular position of the images. Furthermore, we analyse the higher-order images that emerge when lensing occurs around a black hole embedded in a uniform plasma. In this work, we analytically study the time delay for strong gravitational lensing in plasma, including contributions from geometric delay along a bent trajectory in both gravity and plasma, it is conceivable that the ray may be subject to a delay within the gravitational field of the lens, in addition to a dispersion delay that is triggered by the deceleration of light in the medium. In this paper, an expression for the deflection angle is derived in a non-Schwarzschild space-time in the weak field regime in the presence of a plasma. It is demonstrated that this expression depends on the frequency of electromagnetic waves, the gravitational mass , and the deformation parameter .